CHROMATOGRAPHIC AND SPECTROPHOTOMETRIC ANALYSIS OF BIOACTIVE COMPOUNDS FROM CAYRATIA TRIFOLIA (L.) STEM - Sowmya, Sundaram; Perumal, Palanisamy Chella; Gopalakrishnan, Velliyur Kanniappan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was to analyze the bioactive compounds from stem ethanolic extract of Cayratia trifolia by FTIR, HPTLC and GC-MS techniques. Methods: The FTIR was applied and infrared spectrum in mid-infrared region 4000-400 cm-1 was used, HPTLC fingerprinting profiles was done by using Hamilton syringe and CAMAG LINOMAT 5 instrument and GC-MS analysis of stem ethanolic extract of Cayratia trifolia (L.) was performed using the equipment Agilent technologies 7890 A. Results: The FTIR analysis identified the functional groups such as amine, acid, alkane, ketone acyclic, carbonyl, aromatic, ester and alkene. HPTLC fingerprinting profile proves the presence of alkaloids, flavonoids, glycosides, saponin and steroids. GC-MS revealed the presence of various compounds like hexadecanoic acid-ethylester, phytol, tetratetracontane, stigmasterol, nonacosane and octadecane-1-bromo-in stem ethanolic extract of Cayratia trifolia. Conclusion: In conclusion, Cayratia trifolia plant stems ethanolic extract holds more bioactive compounds that may lead to the development of novel drug against various diseases and disorders. Keywords: Cayrtaia trifolia, FTIR Spectroscopy, HPTLC analysis, GC-MS technique, Bioactive compound